Land Asset Management Strategy Optimization in SOEs: APJ PT PLN (Persero) Tasikmalaya - Putri Dewi Purnama (Politeknik Siber Cerdika Internasional, 2026)
Background: PT PLN (Persero) Distribution of West Java and Banten (DJBB) owns idle land assets covering 7,068 m² located on Jalan Ahmad Yani, Tasikmalaya City, which have not been productively utilized since acquisition in 1993. The existence of unoptimized SOE assets burdens state finances and contradicts the Ministry of SOEs’ directive to maximize asset productivity. SWOT analysis provides a systematic framework for identifying strategic factors that can guide effective land asset management decisions. Objective: This study aims to analyze the internal and external environment in order to optimize the utilization of APJ land assets of PT Perusahaan Listrik Negara (Persero) Distribution of West Java and Banten (DJBB) located in Tasikmalaya City. Methods: This study employs a descriptive case study approach using both primary data (observation and interviews with asset management supervisors) and secondary data (company documents and regulations). Data were analyzed sequentially through IFAS, EFAS, SFAS, and SWOT matrix to identify internal and external strategic factors affecting land asset optimization. Results: The IFAS analysis yielded a total weighted score of 2.55 (strengths: 1.92; weaknesses: 0.63), while the EFAS analysis produced a score of 2.57 (opportunities: 1.97; threats: 0.60). Key internal strengths include clear organizational coordination, strategic land physical condition, and supportive company policy. Weaknesses include limited budget allocation, absence of self-investment, and insufficient human resources in the non-installation asset management section. External opportunities comprise ease of licensing, growing lodging demand, and government support for accommodation development. Threats include economic instability, low NJOP land valuation, limited public transportation access, and competitive market pressure. Conclusion: Based on the results of the SWOT analysis, strategies that can be applied include integrated SO, WO, ST, and WT strategies to support the optimization of land assets effectively and sustainably.